2021
DOI: 10.1371/journal.pone.0245611
|View full text |Cite
|
Sign up to set email alerts
|

Testing the effect of pollen exine rupture on metabarcoding with Illumina sequencing

Abstract: Pollen metabarcoding has received much attention recently for its potential to increase taxonomic resolution of the identifications of pollen grains necessary for various public health, ecological and environmental inquiry. However, methodologies implemented are widely varied across studies confounding comparisons and casting uncertainty on the reliability of results. In this study, we investigated part of the methodology, the effects of level of exine rupture and lysis incubation time, on the performance of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Other studies have applied capture enrichment which led to more accurate results avoiding PCR biases 40 . In addition, pollen structure can lead to over and under-representation of some taxa as demonstrated by previous studies 41 . Studies investigating predefined mock communities have attempted to give insight to quantitative issues 42 44 , but more controlled experiments with detailed knowledge of the eDNA ecology and simulations in all ecosystems would be needed to correlate the observed with the true abundance 42 .…”
Section: Discussionmentioning
confidence: 86%
“…Other studies have applied capture enrichment which led to more accurate results avoiding PCR biases 40 . In addition, pollen structure can lead to over and under-representation of some taxa as demonstrated by previous studies 41 . Studies investigating predefined mock communities have attempted to give insight to quantitative issues 42 44 , but more controlled experiments with detailed knowledge of the eDNA ecology and simulations in all ecosystems would be needed to correlate the observed with the true abundance 42 .…”
Section: Discussionmentioning
confidence: 86%
“…There are off-the-shelf kits that work well, along with cheaper extraction methods based on phenol and chloroform; acetone-based DNA isolation has also been effective (Gouker, Guo, & Pooler, 2020). Some studies have shown that it is possible to extract and sequence DNA from pollen without a lysing step (Swenson & Gemeinholzer, 2021). The high-throughput capabilities of DNA metabarcoding are reliant on the addition of sample-specific nucleotides which allow the identification of hundreds of individual samples following pooling into a single sample sent for sequencing (multiplexing).…”
Section: Monitoring Impacts On Human Healthmentioning
confidence: 99%
“…These standards can then be applied when designing a project and when assessing papers during peer-review. Some methods for the various steps involved in pollen DNA metabarcoding have been compared (Swenson & Gemeinholzer, 2021;Tommasi, Ferrari, Labra, Galimberti, & Biella, 2021), however, there remains a lot of work to be done before any general recommendations can be made.…”
Section: Monitoring Impacts On Human Healthmentioning
confidence: 99%
“…Numerous DNA isolation methods exist which can influence the quality of the DNA template [124,125]. Membrane-based isolation techniques are most commonly used for pollen metabarcoding studies, providing a fast and simple way of yielding DNA, although are costly [124].…”
Section: Dna Extractionmentioning
confidence: 99%